THE VALIDITY AND RELIABILITY OF FOUR-TIER FORMAT MISCONCEPTION DIAGNOSTIC TEST INSTRUMENT FOR MOMENTUM AND IMPULSE CONCEPTS - HANIFAH, LAILATUL; ULFAH ERMAWATI, FRIDA (Inovasi Pendidikan Fisika, 2019)
Misconception is the main problem that often occurs in physics concepts including in the concepts of Momentum and Impulse. Misconceptions that experienced by students can be identified using a four-tier format of misconception diagnostic test. This study aims, first, to develop a misconception diagnostic test instrument using four-tier format for Momentum and Impulse concepts. Second, to determine the validity and reliability of the developed instrument. Twenty numbers of test items has been developed. The theoretical validity was obtained by asking 3 physics lectures to evaluate the content, the construct and the language of the instrument. While the empirical validity and the reliability of the instrument was examined by 65 students from SMAN 4 Sidoarjo. The result shows that 94,4% of the theoretical validity was achieved. False positives and false negatives was 6,3% and 6,1% indicate that the instrument was empirically valid. The reliability coefficient (rexp) was 0,61 which is bigger the rtable = 0,24, showing that the instrument was reliable.Keywords : Misconception, Momentum dan Impulse, Four-Tier Misconception Diagnostic Test.